Transmission of wave packets through open mesoscopic systems - Ivanov, N.; Skalozub, V. (Вопросы атомной науки и техники, 2012)
Tunneling of the wave packets having rectangular and Gaussian forms through a quantum diode is investigated. By using the potential of the system the S-matrix for this structure is obtained and the analytic expressions describing the form of the transmitted pulse are calculated. These analytic solutions are compared with the numeric ones. An excellent coincidence is detected. The time-delay for the Gaussian pulse tunneling through the quantum dot is investigated in details. На основе решения уравнения Липпманна-Швингера для возмущенного потенциала рассчитывается матрица рассеяния туннельного диода. Используя формализм S-матрицы и модифицированный метод седловой точки, аналитически рассчитывается форма волнового пакета, выходящего из квантовой точки при подаче на нее пакетов гауссовой и прямоугольной форм. Найдена и проиллюстрирована зависимость времени задержки сигнала гауссовой формы при туннелировании для случая квантовой точки. На основі розв’язку рівняння Ліппманна-Швінгера для збуреного потенціалу розраховано матрицю розсіювання тунельного діоду. Користуючись формалізмом S-матриці та модифікованого методу сідлової точки, аналітично розраховується форма хвильового пакету, що виходить з квантової точки при подаванні на неї пакетів гауссової та прямокутної форм. Знайдено та проілюстровано залежність часу затримки сигналу гауссової форми при тунелюванні для випадку квантової точки.